Synthesis, characterization, antimicrobial and cytotoxicity evaluation of quaternary cadmium (II)-quercetin complexes with 1, 10-phenanthroline or 2, 2'-bipyridine ligands. Issue 1 (1st January 2020) - Srivastava, Tanu; Mishra, Sunil Kumar; Tiwari, Om Prakash; Kumar, Avinash; Tiwari, Kavindra Nath; Kumar, Pradeep; Dixit, Jyoti; Kumar, Jitendra; Singh, Amit Kumar; Verma, Pooja; Saini, Rajesh; Singh, Angaraj; et al.
Abstract: This study reports the synthesis and antibacterial evaluation of two novel complexes, [Cd (Q) (Bpy) (CH3 COO)2, complex 1] and [Cd (Q) (Phen) (CH3 COO)2, complex 2], based on quercetin ligand. The method of synthesis was by reacting natural flavonoid quercetin (Q) with a good chelator (Bpy = 2, 2'-bipyridine, Phen= 1, 10-phenanthroline and Q = quercetin) and metal ions. The produced metal complexes were studied in the solid state by Fourier-transform infrared (FTIR) spectroscopy and in solution by UV-Vis absorption. Further analysis included high resolution mass spectrometry (HRMS) for confirmation. To understand the nature and coordination of quercetin and its metal complexes, density functional theory (DFT) calculation was performed. The scavenging (DPPH radical), antibacterial, MTT, enzymatic and non-enzymatic antioxidant activity assay, cytotoxicity assay (fluorescence study) were done and quercetin was used for comparison. Both complex 1 and complex 2 induced loss of cell viability via impairment of metabolic activity, leakage of intracellular proteins, and increased oxidative stress. The free-radical scavenging activity of complex 2 (IC50 340.175 µg/mL) was statistically significantly more potent than that of complex 1. The MIC values of complex 2 (7.80 µg/mL Escherichia coli, 15.62 µg/mL Staphylococcus aureus ) were higher as compared to complex 1 and quercetin in both test microorganisms. There was inhibition of cell proliferation in Escherichia coli treated with 2 µg/mL of complex 2, whereas Staphylococcus aureus did not show inhibition at this concentration. The cytotoxicity screening on MG 63 cell line showed that the compounds were safe up to 500 mg/L.